Analysis of the Effectiveness of E-Books in Increasing Students' Digital Literacy - Rejeki Tarigan, Jenheri; Kembaren, Bella Pitaloka Br; Fionasari, Richa; Pambudi, Nanda; Hartono, Rumanti (Journal Emerging Technologies in Education, 2024)
Background. The digital era makes education require more sophisticated literacy skills to keep up with the era. The ability to search, access, manage, present, and communicate with digital objects is an ability in digital literacy. Books as reading materials can now be accessed through digital, called E-books. The existence of E-books will bring new changes in the way students learn. The presence of E-books will provide convenience, affordability, and availability. Purpose This study aims to measure the effectiveness of using ebooks in improving students' digital literacy. It also analyzes the factors that influence the effectiveness of using E-books. The presence of E-books as literacy media will be analyzed how influential it is on students' ability to search, access, manage, present and communicate using digital information. Method. The method used in this research is quantitative. The data obtained is the number of responses. The data obtained was taken from the distribution of questionnaires containing questions and statements regarding the effectiveness of E-books in improving students' digital literacy. The statements presented in the questionnaire are a form of google formula called google from. The data will be processed through SPSS which was previously inputted into excel. Results. The results of this study state that the use of E-books as digital reading materials will provide facilities for access, distribution, and consumption of reading materials. The practicality offered will make it easier for educators and students to access it. E-books provide interactive features to enhance the reading experience. In addition, E-books will provide long-distance support in online learning. But of course every advantage has disadvantages or limitations in the use of digital technology. Conclusion This research can be concluded that E-books as reading materials used by teachers and students must be monitored. Analyzing the use of E-books will be useful for identifying inhibiting factors or supporting factors in the world of education. It is also necessary to analyze the effectiveness of using E-books to improve the quality of student literacy. Teachers, parents and formal institutions including students themselves will play an active role in the successful use of E-books in improving digital literacy.